CHALLENGES AND STRATEGIES: THE IMPLEMENTATION OF CHARACTER EDUCATION IN INDEPENDENT CURRICULUM AT ISLAMIC SENIOR HIGH SCHOOL - Sayuti, Lalu; Iswantir; Salmiwati; Khamim, Siti; Zulfiyani, Muhammad (INTIHA: Islamic Education Journal, 2024)
Character education becomes the main focus of Islamic education at Islamic Senior High School (MAN) as an effort to form a generation of young people with good qualities and morals. This article explores the main problem faced in the implementation of education character in Madrasah Aliyah and effective strategies for overcoming challenges. A review of literature, study cases, and articles also identify the role of important stakeholders, such as teachers, parents, and communities, in strengthening the character of students. This analysis gives an outlook deep about how Madrasah Aliyah can become an institution of effective education in the form of appropriate character with Islamic values in the modern era. The purpose of implementing education character at tMadrasah Aliyah curriculum is to form Madrasah Aliyah students in order to become individuals who own strong Islamic characters, such as honesty, discipline, responsibility, tolerance, and work hard that are appropriate to the teachings of Islam. The novelty of this study is the development of Independent Curriculum in which the innovation of integrated curriculum in a holistic way between education, character, and learning academics, so values and character become an integral part of every lesson.